The increased effectiveness of loaded versus unloaded plyometric jump training in improving muscle power, speed, change of direction, and kicking-distance performance in prepubertal male soccer players - Negra, Y.; Chaabene, H.; Sammoud, S.; Prieske, O.; Moran, J.; Ramirez-Campillo, R.; Nejmaoui, A.; Granacher, U. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine the effects of loaded (LPJT) versus unloaded plyometric jump training (UPJT) programs on measures of muscle power, speed, change of direction (CoD), and kicking-distance performance in prepubertal male soccer players. Methods: Participants (N=29) were randomly assigned to a LPJT group (n=13; age=13.0 [0.7] y) using weighted vests or UPJT group (n=16; age=13.0 [0.5] y) using body mass only. Before and after the intervention, tests for the assessment of proxies of muscle power (ie, countermovement jump, standing long jump); speed (ie, 5-, 10-, and 20-m sprint); CoD (ie, Illinois CoD test, modified 505 agility test); and kicking-distance were conducted. Data were analyzed using magnitude-based inferences. Results: Within-group analyses for the LPJT group showed large and very large improvements for 10-m sprint time (effect size [ES]=2.00) and modified 505 CoD (ES=2.83) tests, respectively. For the same group, moderate improvements were observed for the Illinois CoD test (ES=0.61), 5- and 20-m sprint time test (ES=1.00 for both the tests), countermovement jump test (ES=1.00), and the maximal kicking-distance test (ES=0.90). Small enhancements in the standing long jump test (ES=0.50) were apparent. Regarding the UPJT group, small improvements were observed for all tests (ES=0.33-0.57), except 5- and 10-m sprint time (ES=1.00 and 0.63, respectively). Between-group analyses favored the LPJT group for the modified 505 CoD (ES=0.61), standing long jump (ES=0.50), and maximal kicking-distance tests (ES=0.57), but not for the 5-m sprint time test (ES=1.00). Only trivial between-group differences were shown for the remaining tests (ES=0.00-0.09). Conclusion: Overall, LPJT appears to be more effective than UPJT in improving measures of muscle power, speed, CoD, and kicking-distance performance in prepubertal male soccer players.